Human predation contributed to the extinction of the Australian megafaunal bird Genyornis newtoni ~47 ka - Miller, Gifford; Magee, J.; Smith, M.; Spooner, N.; Baynes, A.; Lehman, S.; Fogel, M.; Johnston, H.; Williams, D.; Clark, P.; Florian, C.; Holst, R.; et al. (Macmillan Publishers Limited, 2016)
Although the temporal overlap between human dispersal across Australia and the disappearance of its largest animals is well established, the lack of unambiguous evidence for human–megafauna interactions has led some to question a human role in megafaunal extinction. Here we show that diagnostic burn patterns on eggshell fragments of the megafaunal bird Genyornis newtoni, found at >200 sites across Australia, were created by humans discarding eggshell in and around transient fires, presumably made to cook the eggs. Dating by three methods restricts their occurrence to between 53.9 and 43.4 ka, and likely before 47 ka. Dromaius (emu) eggshell occur frequently in deposits from >100 ka to present; burnt Dromaius eggshell first appear in deposits the same age as those with burnt Genyornis eggshell, and then continually to modern time. Harvesting of their eggs by humans would have decreased Genyornis reproductive success, contributing to the bird’s extinction by ~47 ka.